Association of heat shock protein70-2 (HSP70-2) gene polymorphism with obesity. (1st November 2016) - Mardan-Nik, Maryam; Pasdar, Alireza; Jamialahmadi, Khadijeh; Avan, Amir; Mohebati, Mohsen; Esmaily, Habibollah; Biabangard-Zak, Atefeh; Afzal Javan, Fahimeh; Rivandi, Mahdi; Ferns, Gordon A.; Ghayour-Mobarhan, Majid
Abstract: Background : Obesity is a major risk factor of chronic-diseases, including cardiovascular-diseases (CVD). Increasing evidence is showing the association of heat-shock protein (HSP) with type-2 diabetes and CVD; however, there is little data on the relationship between the genetic-polymorphisms of HSP70-2 with obesity. Aim : The present study has investigated the association between 1267HSP70-2 genetic polymorphism and obesity in an Iranian population with 317 subjects. Subjects and methods : Anthropometric parameters and biochemical measurements were measured in all the samples, while genotypes were determined using PCR-RFLP. Univariate/multivariate analyses were conducted to explore the relationship between the genetic-polymorphisms and obesity. Results : The data showed a significant association between 1267HSP70-2 polymorphism in obese subjects, compared to the non-obese group. Moreover, it was observed that this polymorphism was associated with obesity in the CAD + group, which had a high BMI compared to non-obese controls. Conclusion : The 1267HSP70-2 polymorphism is associated with obesity in an Iranian population, supporting a possible potential genetic link between obesity and cardiovascular diseases.